Implementation of the values of compassion and politeness as the basis for the formation of civic virtue among students of PGRI Wiranegara University - Nuria Sinta; Yuniar Mujiwati; Innayatul Laili (Institute Of computer Science (IOCS), 2026)
In campus life, students often display behavior lacking in friendliness and courtesy during their interactions. This hinders the development of holistic civic virtue. Conducting this research is crucial because the decline in interpersonal ethics within higher education has the potential to undermine the academic climate and democratic values. Unlike previous studies that largely focused on formal moral education, the novelty of this research lies in its examination of compassion and practical courtesy as the primary foundations of student civic virtue. The researchers employed a qualitative method involving in-depth interviews with informants selected through purposive sampling. The study was conducted at PGRI Wiranegara University, and all data obtained were analyzed using qualitative content analysis. Specific findings indicate that students are experiencing a crisis of courtesy driven by high academic pressure and a lack of inclusive spaces for social interaction. Furthermore, the study reveals that an overly competitive campus environment tends to diminish empathetic sensitivity among students in their daily lives. These findings highlight the need to strengthen practical aspects through case-study-based learning, the creation of an institutional environment that fosters fairness, and the adjustment of academic policies to ensure they do not stifle the expression of civic virtue. Academically, this research contributes to enriching the literature on the sociology of education and offers a new approach for developing character-based curricula in higher education.